EXPLORING MARKETING-BASED REAL EARNINGS MANAGEMENT IN ESG-ORIENTED FIRMS - Nurul Ittaqullah (Jurusan Akuntansi, Universitas Halu Oleo, 2026)
Environmental, social, and governance (ESG) orientation has become a critical component of corporate strategy, encouraging firms to pursue long-term value creation while maintaining accountability to diverse stakeholders. However, firms remain subject to short-term earnings pressures that may motivate managers to engage in real earnings management (REM) through operational decisions. Among various discretionary expenditures, marketing investments represent a unique channel of REM because they are strategically important yet easily adjustable. This study explores the role of marketing investments as a channel of REM in ESG-oriented firms through a systematic literature review. Following the PRISMA framework, the review synthesizes studies published between 2015 and 2026 across the fields of accounting, marketing, sustainability, and corporate governance. The findings indicate that while ESG-oriented firms generally exhibit stronger governance structures and lower tendencies toward earnings management, ESG commitments do not necessarily eliminate incentives for opportunistic managerial behavior. Marketing investments, particularly digital marketing expenditures, emerge as a potentially important but underexplored mechanism through which firms may balance earnings targets and stakeholder expectations. This review contributes by integrating fragmented literature and proposing future research directions on marketing-based REM within ESG-oriented organizations.